2009
DOI: 10.1099/vir.0.016576-0
|View full text |Cite
|
Sign up to set email alerts
|

Classical swine fever virus infection protects aortic endothelial cells from pIpC-mediated apoptosis

Abstract: Classical swine fever virus (CSFV) causes severe disease in pigs associated with leukopenia, haemorrhage and fever. We show that CSFV infection protects endothelial cells from apoptosis induced by the dsRNA mimic, pIpC, but not from other apoptotic stimuli, FasL or staurosporine. CSFV infection inhibits pIpC-induced caspase activation, mitochondrial membrane potential loss and cytochrome c release as well as the pro-apoptotic effects of truncated Bid (tBid) overexpression. The CSFV proteins N pro and E rns bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…We suggest that it is feasible that, to ensure efficient viral replication, the CSFV N pro product targets the apoptotic response through its interaction with HAX-1. CSFV infection inhibits dsRNA-induced apoptosis at a number of apoptotic checkpoints, preventing caspase-8 activation and loss of mitochondrial membrane potential (Johns et al, 2010). N pro contributes to the antagonism of dsRNA-mediated apoptosis; however the underlying mechanism has not been determined (Johns et al, 2010;Ruggli et al, 2003Ruggli et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We suggest that it is feasible that, to ensure efficient viral replication, the CSFV N pro product targets the apoptotic response through its interaction with HAX-1. CSFV infection inhibits dsRNA-induced apoptosis at a number of apoptotic checkpoints, preventing caspase-8 activation and loss of mitochondrial membrane potential (Johns et al, 2010). N pro contributes to the antagonism of dsRNA-mediated apoptosis; however the underlying mechanism has not been determined (Johns et al, 2010;Ruggli et al, 2003Ruggli et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…CSFV infection inhibits dsRNA-induced apoptosis at a number of apoptotic checkpoints, preventing caspase-8 activation and loss of mitochondrial membrane potential (Johns et al, 2010). N pro contributes to the antagonism of dsRNA-mediated apoptosis; however the underlying mechanism has not been determined (Johns et al, 2010;Ruggli et al, 2003Ruggli et al, , 2005. In this study, no decrease in HAX-1 levels was observed in PK-15 cells following treatment with dsRNA, indicating that N pro does not inhibit dsRNA-mediated apoptosis by preventing HAX-1 degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study reveals that, in addition, HSV R1s protect HSV-infected cells against poly(I ⅐ C)-induced caspase 8 activation, possibly through their interaction with RIP1 and caspase 8. Interestingly, this type of viral protection is not restricted to HSV, since a recent study showed that infection with the classical swine fever virus, a positive-sense RNA virus, protects endothelial cells from extracellular poly(I ⅐ C)-mediated apoptosis, notably by inhibiting caspase 8 activation (34). Thus, viral inhibition of dsRNAmediated apoptosis could be a strategy used by several viruses to ensure host cell survival and, therefore, efficient replication and spreading.…”
Section: Discussionmentioning
confidence: 99%